2008
DOI: 10.1002/pat.1153
|View full text |Cite
|
Sign up to set email alerts
|

Flame retardancy study on magnesium hydroxide associated with clays of different morphology in polypropylene matrix

Abstract: Fire retardancy behavior of polypropylene–magnesium hydroxide–clay composites of different morphologies is presented. Layer‐ and needle‐like clay nanoparticles in natural and organically surface modified form have been compared. Fire retardant performance of the composites was evaluated by conical combustor and by horizontal burning test, while the structure was characterized by SEM. Rheological analysis of varied temperature provided further information about the strength of the formed combustion residue. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
49
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(55 citation statements)
references
References 26 publications
0
49
0
Order By: Relevance
“…also studied the flame retardancy performance of CNT filled PP and managed to reduce the PHRR from 2755 kW/m 2 to 760 kW/m 2 for PP and PP/CNT, respectively. Marosfoil et al . studied the flame retarding effects of magnesium hydroxide, MMT, and sepiolite nanoclay in PP.…”
Section: Resultsmentioning
confidence: 99%
“…also studied the flame retardancy performance of CNT filled PP and managed to reduce the PHRR from 2755 kW/m 2 to 760 kW/m 2 for PP and PP/CNT, respectively. Marosfoil et al . studied the flame retarding effects of magnesium hydroxide, MMT, and sepiolite nanoclay in PP.…”
Section: Resultsmentioning
confidence: 99%
“…It can have a surface area as high as 200-300 m 2 /g, lengths of 0.2-4 µm, a width of 10-30 nm and thickness of 5-10 nm [29]. In a previous study, we found that sepiolite has a good flame retardant synergistic effect with magnesium hydroxide in EVA [30] or PP [31]. However, there are few reports about sepiolite use in IFR polypropylene [32,33].…”
Section: Introductionmentioning
confidence: 96%
“…[16][17][18][19] Significant improvements in flammability and combustion parameters were observed when MH and different types of clays were used. 20 Sepiolite has a chainlike structure with the chemical formula Si 12 Mg 8 O 30 (OH) 4 (OH 2 ) 4 8H 2 O, and it has been used for the preparation of polymer composites. 21,22 The structure of sepiolite is quite similar to the structure of MH, and it also contains water of hydration and can be used with MH.…”
Section: Introductionmentioning
confidence: 99%